Kontribusi TNI Manunggal Membangun Desa (TMMD) dan Perguruan Tinggi pada Penyuluhan Koperasi dan UMKM di SMK Gema Bangsa - Kenny Ardillah (Penerbit Goodwood, 2022)
Purpose: Improve small and medium business owners in obtaining understanding provision for business owners from an early age starting from the Gema Bangsa Vocational School, Cikupa District. Method: Expository through giving lectures from speakers sourced from university lecturers in Tangerang Regency who were appointed by the Tangerang Regency Cooperative and Small Medium and Enterprises Service, several lecturers from various universities appointed by the Tangerang Regency Cooperative and MSMEs Service, members of Bintaldam Jaya, and police officers from the Tangerang Police and the Tangerang Transportation Agency. Results: Counseling on Cooperatives and MSMEs carried out in non-physical target activities of the 105th TMMD Kodim 0510/Trs together with the MSME and Cooperatives Service in the hall of Gema Bangsa Vocational School, Cisoka District, Tangerang Regency which was attended by 150 students and went smoothly. Conclusions: There is an increase in understanding for Gema Bangsa Vocational School students who become training participants in solving practice questions related to the basic concepts, benefits, and urgency of cooperatives and increasing students' readiness to play an active role in managing school cooperatives. The 105th Regular TMMD can provide understanding to the community regarding briefing and early recognition of the importance of school cooperatives and the urgency of increasing the number of MSMEs.